2012
DOI: 10.1108/03090561211260068
|View full text |Cite
|
Sign up to set email alerts
|

The relative performance of TV sponsorship versus television spot advertising

Abstract: Research Paper PurposeTo compare the relative performance of TV sponsorships with the industry standard 30-second TV spot advertising on achieving common communication goals. Design/Methodology/ApproachThe two mediums are tested with an experiment using realistic stimuli and target market representative samples and employing 6 brands as both TV sponsors and TV advertisers. FindingsTen seconds of TV sponsoring works almost equally as well as 30-second spots across all measures and brands. While the outright per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
4
22
1
Order By: Relevance
“…This raises serious questions about the credibility and effectiveness of current sponsorship measurement. On the academic front, recent research (Olson & Thjømøe, , ) has attempted to address the difficult issue of media value equivalence. While welcome in terms of focus, the experimental nature of the research design and indeed other limitations acknowledged by the authors make any level of generalization particularly difficult and premature at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…This raises serious questions about the credibility and effectiveness of current sponsorship measurement. On the academic front, recent research (Olson & Thjømøe, , ) has attempted to address the difficult issue of media value equivalence. While welcome in terms of focus, the experimental nature of the research design and indeed other limitations acknowledged by the authors make any level of generalization particularly difficult and premature at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…expectations about the brand's reliability in a risky situation or willingness to rely on the brand to perform its stated functions. Studies have shown that sponsorship can improve a sponsor's brand affect and brand trust (Mazodier and Merunka, 2012;Olson and Thjømøe, 2012).…”
Section: Impacts Of Sponsorship On Brand Affect and Brand Trustmentioning
confidence: 99%
“…While recognizing that all elements of marketing and marketing communications possess different features and capabilities, sponsorship is most often contrasted with media advertising in general (Hastings, ; Hoek et al, ; McDonald, ; Meenaghan ) and indeed with specific aspects of advertising (Olson & Thjømøe, , ; Walliser, ). The comparison of sponsorship and traditional advertising has been previously addressed in terms of a range of discernible differences which included the mutuality of benefit, the consumer interaction process, the comparative nature of the communications process, as well as sponsorship's location at the “leisure end of marketing.” While sponsorship may be different in certain respects, such differences are no impediment to the task of performance measurement and, thus, the “sponsorship is different” argument is largely irrelevant to the need for or ability to undertake proper performance analysis (Meenaghan, ).…”
Section: Is Sponsorship Different?mentioning
confidence: 99%